The role of performance skills in German teacher education: empirical relations between general pedagogical knowledge, communication skills, and grades - Walz, Kristina; Schwabe, Ulrike; Braun, Edith (Frontiers in Education, 2024)
This contribution explores empirical associations between general pedagogical knowledge (GPK), communication skills, and grades in initial teacher education. We assessed the GPK and communication skills of 105 student teachers in Germany, using a knowledge test and a performance-based assessment. Empirical results show a significant correlation between GPK and grades but not between communication skills and grades. GPK is associated with the number of semesters, while communication skills are associated with age. We discuss the learning objectives of initial teacher education in higher education in the light of our results.